33-year follow-up after valvular surgery for carcinoid heart disease. (25th November 2020) - Bergsten, J; Albage, A; Flachskampf, F
Abstract: Background: Valvular surgery for carcinoid heart disease (CaHD) has been found to improve long-term prognosis. Experience is limited and questions about single versus double-valve surgery as well as selection of prosthetic valves remain under debate. Purpose: We reviewed the surgical experience after valvular surgery for CaHD in our institution, which is a national referral center. Methods: We reviewed clinical records and echocardiograms. Perioperative death was defined as mortality within 30 days of operation. Results: Sixty consecutive patients (32 men, 62±9 years) underwent valve surgery between 1986 and 2019, of whom 59/60 had an intestinal carcinoid disease with hepatic metastases. Mean time from diagnosis to heart surgery was 3.8±3.7 years. Preoperatively, 6 patients were in NYHA class I/II, the others were in class III or IV. All 60 surgical procedures involved tricuspid valve replacement (TVR). In 47 cases, the pulmonary valve was treated surgically: Early in the series, five patients underwent pulmonary valvotomy or commissurotomy, and more recently, 42 patients received pulmonary valve replacement (PVR). All valves were replaced with bioprostheses, except for one pulmonary homograft. Concomitant significant aortic and mitral regurgitation occurred in 2 patients who received quadruple valve replacement. Two re-operations were performed due to degeneration of bioprostheses. Mean hospital stay was 13±9 days. Overall 30-day mortality was 11.6% (n=7) but was reduced to 8.3% in the last decade. The overall median survival was 2.2 years. Maximal survival free of reoperation was 18 years, and maximal survival for a single patient was 21 years. Median survival for combined TVR and PVR was significantly better than for single TVR or TVR combined with pulmonary valvotomy (3.0 years vs. 0.94 years, respectively, p=0.02; see Figure). Preoperatively, left ventricular ejection fraction (EF) was normal in 83%. Severe tricuspid regurgitation was always present. The right ventricle (RV) was dilated (RVD1 49 mm ± 5 mm) as well as the right atrium (60±16 ml/m 2 ). The TAPSE was in normal range (17 to 29 mm). Pulmonary regurgitation was mild, moderate, severe, or indeterminate in 6%, 26%, 51%, and 17% respectively. In 17% the transpulmonary velocity was >2.5 m/s, indicating stenosis. On last available postoperative echo (mean time 2.1 years) EF was found unchanged. RV diameter was nearly normalized (RVD1 41 mm ± 5 mm). TAPSE was reduced (12 mm ± 4 mm). No significant regurgitation was detected in any TVR. There was significant stenosis (mean gradient >5 mmHg) in 23% of the TVR. No regurgitation of significance was detected in any PVR. A mean gradient >20 mmHg was found in 11% of the PVR. Conclusions: While perioperative risk of valve replacement in CaHD remains substantial, this study shows relatively favourable outcomes of surgical valve replacement with bioprostheses. PVR together with TVR had better outcomes than those undergoing TVR only. Funding Acknowledgement: Type of funding source: Public hospital(s). Main funding source(s): Department of Medical Sciences, Uppsala University. Department of Surgical Sciences, Uppsala University